CHILD ALLERGIC RHINITIS: DOES THERAPY AFFECT PATIENTS' COGNITIVE FUNCTIONS AND QUALITY OF LIFE - A.Yu. Tomilova; R.M. Torshkhoeva; L.S. Namazova; L.M. Kuzenkova (Union of pediatricians of Russia, 2008)
According to world health organization data, allergic reactions occur more frequently nowadays, with allergic rhinitis, including its perennial form, being the most common allergy among children. Basing on their own research, the authors demonstrate that severe clinical courses of this disease significantly affect cognitive functions and quality of life of children that suffer from this disease. The article features data that demonstrates positive effect of pathogenetic therapy on these factors of life of patients with perennial allergic rhinitis.Key words: allergic rhinitis, cognitive function, quality of life, treatment, antihistaminic, children.